2016
DOI: 10.1093/ehjci/jew116
|View full text |Cite
|
Sign up to set email alerts
|

PET-measured longitudinal flow gradient correlates with invasive fractional flow reserve in CAD patients

Abstract: The observed close correlation between a longitudinal MBF gradient during hyperaemic flows and invasively measured FFR suggests the longitudinal flow gradient as an emerging non-invasive index of flow-limiting CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 37 publications
0
45
0
Order By: Relevance
“…For the assessment of coronary circulatory function, PETmeasurements MBFs at rest and its response various forms of vasomotor stress can be conducted (1,5,8,9). The latter may include bicycle exercise, dobutamine stress, sympathetic stimulation with cold pressor testing (CPT), vascular smooth muscle cell relaxation at the site of the coronary arteriolar vessels, or heterogenous responses of MBF in more apical and more basal regions of the left ventricle as a possible noninavsive index of epicardial vasomotion.…”
Section: Pet-determined Parameters Of Coronary Circulatory Dysfunctiomentioning
confidence: 99%
“…For the assessment of coronary circulatory function, PETmeasurements MBFs at rest and its response various forms of vasomotor stress can be conducted (1,5,8,9). The latter may include bicycle exercise, dobutamine stress, sympathetic stimulation with cold pressor testing (CPT), vascular smooth muscle cell relaxation at the site of the coronary arteriolar vessels, or heterogenous responses of MBF in more apical and more basal regions of the left ventricle as a possible noninavsive index of epicardial vasomotion.…”
Section: Pet-determined Parameters Of Coronary Circulatory Dysfunctiomentioning
confidence: 99%
“…The diagnostic and prognostic value of flow and flow reserve measured using dynamic cardiac PET perfusion imaging is now well established (11,19,20,(23)(24)(25)(26)(27)(28)(29)(30)(31) and presents the advantage for excluding balanced ischemia due to 3-vessel CAD. (19, 20, 23-31,) ASNC guidelines note that quantification of MBF using PET appears to be most useful in the following circumstances (11): "1) patients without a known history of CAD who present with symptoms suspect for myocardial ischemia; 2) patients with known CAD, in whom more specific physiological assessment is desired; 3) Identifying [patients with] an increased suspicion for multi-vessel CAD; 4) to assess possible microvascular dysfunction; 5) heart transplant patients when there is a question of transplant vasculopathy".…”
Section: How To Differentiate Microvascular Disease From 3-vessel Dismentioning
confidence: 99%
“…Patients with HIV on stable anti-retroviral therapy were shown to have reduced peak MBF under stress conditions with preserved CFR [27]. A study by Valenta et al demonstrated a close correlation between the longitudinal MBF and invasively measured fractional flow reserve under conditions of hyperemia for the assessment of a coronary stenosis [28]. In the future, it will be important to pursue more studies to attempt to use CFR as both a tool to assist with clinical decision-making and a marker of cardiac health and correlate improvement in CFR with a reduction in primary cardiovascular outcomes.…”
Section: Positron Emission Tomographymentioning
confidence: 99%